Design of a Relay Circuit Based LCC Bell for the IAIN Pontianak Quiz Competition - Havizul Havizul (PTE FTK UIN Ar-Raniry, 2023)
In order to commemorate its second anniversary, the Mathematics Tadris Study Program at IAIN Pontianak organized a quiz competition between West Kalimantan schools in December 2022. The difficulty in obtaining the Quiz Buzzer, despite the fact that it is a crucial component in conducting the Quiz Contest, was one of the challenges encountered when attempting to carry out the event. Without the Quiz Buzzer, the contest question session would not have been held. This study was done to develop a quiz buzzer for a Tadris Mathematics Study Program quiz competition based on a DC 12V relay circuit. The needs identification, design, development, and testing phases make up the four phases of the methodology used in this study. A truth table, which represents the operation or functionalities of the quiz buzzer circuit, and a wiring plan known as a ladder diagram was produced during the design phase. A comprehensive schematic for the quiz buzzer circuit was created throughout the development stage. While the Proteus software's simulation capability is used to do testing. The software simulation test results demonstrate that the quiz buzzer circuit is functioning correctly in accordance with the requirements of quiz competitions.